Mass and stress changes in the Menderes Massif (Western Anatolia, Turkey). (1st December 2016) - Çırmık, Ayça; Pamukçu, Oya; Akçığ, Zafer
Graphical abstract: Highlights: The mass and stress changes were examined in the Menderes Massif with the help of GNSS and gravity data. The Coulomb stress changes of the tectonic structures were calculated with GNSS velocities. The stabilities of the main tectonic structures of study area were interpreted. The unstable regions were found to be coherent with high heat flow values. Abstract: Comparing the results of the microgravity and GNSS measurements is useful for understanding the vertical displacements of the plates. In this study, for determining the geodynamical behaviors of seismically active tectonic structures of Gediz and Büyük Menderes grabens which are located in Western Anatolia (Turkey) graben system, the mass changes were examined by processing of GNSS and microgravity data. Besides, after modeling the GNSS velocity by Coulomb stress analysis, the stress distributions were investigated for these models. Therefore, first of all, the changes of gravity and the vertical components of GNSS velocity values were evaluated together with a statistical method. Secondly, GNSS velocities were calculated relative to the main tectonic structures and the stress changes of tectonic structures were obtained at different depths with Coulomb stress analysis by using these velocities and all results were evaluated with the earthquakes that had occurred in the study area. Consequently, the crustal movements of the areas located at the GNSS stations and their surroundings were put forwarded as in compensation or uncompensation concept of surface and subsurface loadings due to the mass or groundwater effects by using both microgravity and GNSS measurements, as an initial study on Western Anatolia graben system.